Association between all-cause mortality and insurance status transition among the elderly population in a rural area in Korea: Kangwha Cohort Study. Issue 5 (May 2015) - Jang, Sung-In; Yi, Sang-Wook; Sull, Jae-Woong; Park, Eun-Cheol; Kim, Jae-Hyun; Ohrr, Heechoul
Highlights: Transition from National Health Insurance (NHI) to Medicaid increases mortality risk. Transition from Medicaid to NHI may mitigate mortality risk. People remaining on Medicaid have higher mortality risk than those covered by NHI. Policy makers should strengthen coverage for Medicaid in Korea. Abstract: The study purpose was to examine the association between health insurance transition and all-cause mortality. 3206 residents in Korea who participated in two surveys in 1985 and 1994, were followed-up during 1994–2008. Adjusted hazard ratios (aHR) were calculated using Cox hazard model. Participants were divided into four groups by insurance transition (the "National Health Insurance (NHI)–NHI", "NHI–Medicaid", "Medicaid–NHI", and "Medicaid–Medicaid" groups), where NHI–Medicaid means participants covered by NHI in 1985 but by Medicaid in 1994. For men covered by NHI in 1985, the mortality risk in the NHI–Medicaid was higher (aHR = 1.47) than in the NHI–NHI. For men and women, covered by Medicaid in 1985, aHR was non-significantly lower in the Medicaid–NHI than in the Medicaid–Medicaid. When four groups were analyzed together, men in the Medicaid–Medicaid (aHR = 1.67) and NHI–Medicaid (aHR = 1.46) groups had higher mortality risk than males in the NHI–NHI, whereas no significant difference was observed for females. In conclusion, transition from NHI to Medicaid increases mortality risk, and transition from Medicaid to NHI may mitigate risk, while remaining on Medicaid pose the greatest risk, especially for men. Therefore, policy makers should strengthen coverage for Medicaid. The weak effects of transition from NHI to Medicaid on mortality for women require validation.